Properties of nano Î±gÌ‚ -closed sets - Bhavani, R. (Journal of Global Research in Mathematical Archives(JGRMA), 2018)
Abstract:In this paper, we introduce the notion of nanoÂ  Î±gÌ‚ -closed sets in nano topological spaces and investigate some of their properties.